Rancang Bangun Alat Monitoring Online Temperatur Klem Pada Kubikel 20 KV Berbasis IOT - Muhammad Alan Faza; Agus Kiswantono (Jurnal Teknika, 2022)
Hot spots in 20 kV cubicles often occur, especially at the clamp connections between cables and bus bar conductors. Due to the camp's position in the cubicle, it is not uncommon for the hotspot to be unmonitored. This hotspot phenomenon can be monitored online by utilizing Internet of Things (IoT) technology. Integrating a microprocessor and infrared sensor with a maximum measuring distance of 60 cm has met the safe distance of 20 kV voltage measurement. By being monitored online, if there is a hotspot at the 20 kV cubicle clamp, action will be taken more quickly so that there is no widespread disturbance and damage to the equipment.